A process-oriented quality assurance and organizational performance: a conceptual approach - Hassan, M. G.; Akanmu, Muslim Diekola; Bahaudin, Ahmad Yusni (2018)
The main objective of this study is to develop a life cycle mode for a process-oriented quality assurance in organizational performance of food and beverage companies. As an iterative and dynamic process, quality assurance is interwoven in the production and process of food and beverages in the agro-allied industry. Through the review of literatures in existence, specifically those that focus on procedures, frameworks and methodology, a process oriented framework is developed around non-linear sequential stages presented as: planning (before), design and production (during), post production and delivery (after). The model is approved through an advanced systematic methods employed in collecting, organizing and generating reports about quality assurance for updates or changes. Many studies emphasize that quality assurance needs a friendly environs that take quality as a key factor and a work value for attaining the objectives of an organization. A practical quality assurance model is then proposed by this study that complies with the guide of food and beverage developmental stages. Practical steps are recommended in each stage. There is great potential in the quality assurance model for its transformation from static, the state of after-the-fact to a state of dynamism and iterative state, thereby improving the ongoing self-improvement culture.